Knowledge, Attitudes, and Behaviors of Pregnant Women Regarding Smoking Who Were Admitted to the Obstetrics Clinic of the Bülent Ecevit University Hospital - Cemal Koçak; Mehmet Ali Kurçer; İnan İlker Arıkan (İstanbul Medical Journal, 2015)

(untitled)
Objective: Smoking in pregnancy and postpartum period causes serious healthy risks for fetuses, newborns, and children. The purpose of this study was to determine the prevalence of smoking and associated sociodemographic factors and knowledge, attitude levels, and behaviors of pregnant smokers.Methods: A descriptive study was performed on 335 pregnant women who were admitted to our clinic between March 1 and April 30, 2014. A questionnaire prepared by researchers comprising 24 questions was applied to eligible women. Statistical analysis was performed using SPSS 19 software program. Descriptive statistical data are presented as frequencies, and measurements are presented as mean ± standard deviation. Chi-square test was used for comparison between categorical variables. Mann–Whitney U test and Kruskal–Wallis analysis of variance were used for comparisons between paired groups.Results: A total of 20.5% of pregnant women smoked throughout pregnancy. Education and income status of pregnant women did not have a significant association with smoking during pregnancy (p=0.172 and p=0.203, respectively). Smoking status was compared with pregnancy, breastfeeding, and total knowledge scores. While a significant difference did not exist between pregnancy and total knowledge scores (p=0.126, p=0.051), knowledge scores of breastfeeding was significantly lower in smoking women (p=0.031). Education status and knowledge scores were compared. Each of the three knowledge scores was higher in women with higher education levels (p=0.003, p=0.000, and p=0.001).Conclusion: Smoking during pregnancy is a major health problem. Control frequency should be increased for pregnant smokers and for their babies as well as to aid in the early diagnosis of potential problems. Doctors, nurses, and midwives should remind patients who quit smoking during pregnancy that they should take professional help to not start smoking again in the postpartum period.